Data for dairy farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
workshop on 'The Regional Exchange Network for Market Oriented Dairy Development' in Eastern and Southern African countries held in Harare, Zimbabwe from 4-8 December, 1995